1996
DOI: 10.1212/wnl.47.4.1042
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of epidermal nerves in diabetic neuropathy

Abstract: We describe methods to quantify epidermal nerve fibers (ENFs) in skin biopsy specimens from diabetic candidates for pancreas transplantation and control subjects. ENFs and the dermal-epidermal basement membrane were stained by immunohistochemical methods, imaged with a confocal microscope, and quantified using a neuron tracing system. The number of ENFs per surface of epidermis was diminished in diabetic subjects. ENF number and summed length of all ENFs per volume of epidermis examined were also decreased. Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
327
1
7

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 402 publications
(353 citation statements)
references
References 16 publications
18
327
1
7
Order By: Relevance
“…a lower IENFD than the SOD2 +/+ db/db mice (p < 0.05). The anticipated differences between epidermal nerve fiber densities in diabetic and control animals (regardless of SOD2 expression) were also in accordance with published reports in human patients (Yasuda et al, 1985;Levy et al, 1989;Kennedy et al, 1996;Arezzo, 1999) and experimental models of DN (Christianson et al, 2003).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…a lower IENFD than the SOD2 +/+ db/db mice (p < 0.05). The anticipated differences between epidermal nerve fiber densities in diabetic and control animals (regardless of SOD2 expression) were also in accordance with published reports in human patients (Yasuda et al, 1985;Levy et al, 1989;Kennedy et al, 1996;Arezzo, 1999) and experimental models of DN (Christianson et al, 2003).…”
Section: Discussionsupporting
confidence: 90%
“…The foot pad innervation study in the male C57BL/6J SOD2 +/+ and SOD2 +/− mice confirmed that there was no hind paw neuropathy. This anatomical assessment of neuropathy is part of the standard neuropathy phenotyping recommended by the AMDCC (www.amdcc.org) and is sensitive and reproducible (Levy et al, 1989;Kennedy et al, 1996;Arezzo, 1999). The TRAP values suggest that these mice did not develop significant oxidative stress in the DRG, so we may conclude that loss of one copy of SOD2 was not sufficient to increase oxidative stress in vivo, despite our observations in vitro.…”
Section: Discussionmentioning
confidence: 73%
“…Recent advances in quantitation of epidermal innervation have confirmed that human diabetics have significantly reduced epidermal innervation (McCarthy et al, 1995;Kennedy et al, 1996). Epidermal changes have been correlated with reduced conduction velocity, suggesting that quantitative analysis of cutaneous innervation may be indicative of developing neuropathies (Herrmann et al, 1999;Hirai et al, 2000).…”
mentioning
confidence: 99%
“…Interest in using exogenous neurotrophins to treat diabetic neuropathy in humans has slowed due to the outcomes in clinical trials, but studies in animal models continue to report beneficial effects. Importantly, these studies in rodents point out the diverse actions of neurotrophins on select populations of sensory neurons and that identifying neurotrophin-induced effects require selective and appropriate assessments (reviewed in Apfel, 2002; Lenninger et al, 2004).Recent advances in quantitation of epidermal innervation have confirmed that human diabetics have significantly reduced epidermal innervation (McCarthy et al, 1995;Kennedy et al, 1996). Epidermal changes have been correlated with reduced conduction velocity, suggesting that quantitative analysis of cutaneous innervation may be indicative of developing neuropathies (Herrmann et al, 1999;Hirai et al, 2000).…”
mentioning
confidence: 99%
“…Biopsies were fixed in Zamboni solution for 24 hours and then cryoprotected. 10,11 Thick, 50-m sections were cut vertical to the skin surface, at 90 o to the fingerprint ridges, processed for indirect immunofluorescence, and MCs were quantified as described. 12 Data analyses.…”
mentioning
confidence: 99%